Technology and innovation policies for small and medium-sized enterprises in East Asia - Patarapong Intarakumnerd; Akira Goto (Asian Development Bank Institute (ADBI), 2016)
Policies for stimulating technological development and innovation in small and medium-sized enterprises can be divided into three groups. Supply-side policies aim at increasing firms' incentives to invest in innovation by reducing costs. Demand-side policies are public actions to induce innovation and/or speed up the diffusion of innovation. Systemic policies focus on strengthening interactive learning between actors in innovation systems. Policies can be implemented through various instruments comprising tax incentives, grants or direct subsidies, low-interest loans, and the government's direct equity participation. These instruments have pros and cons. The experiences of four late-industrializing East Asian economies - Taipei,China; Singapore; Malaysia; and Thailand - provide key lessons. Firms at different levels of technological and innovative capability need different policy instruments. The more successful economies have a higher level of flexibility and policy coordination and learning. The amount, duration, and continuity of government supporting schemes are crucial. Policy makers must have a deep understanding of what constitutes innovations and innovation systems, and how they evolve over time. Innovation financing policies require other corresponding policy initiatives to make them successful. Lastly, institutional factors do shape the choices and effective implementation of these policies.
Keywords: D22; L25; O31; 330; technological development; East Asia SMEs; diffusion of innovation; demand-side policies